High-performance membranes with full pH-stability. Issue 16 (26th February 2018) - Daems, Nick; Milis, Sam; Verbeke, Rhea; Szymczyk, Anthony; Pescarmona, Paolo P.; Vankelecom, Ivo F. J.
Abstract : Grafted PVDF membranes were synthesized with improved nanofiltration properties ( R NaCl ≈ 60%) and stability over the full pH range. Abstract : Following current strong demands from, among others, paper, food and mining industries, a novel type of nanofiltration membrane was developed, which displays excellent performance in terms of selectivity/flux with a unique combination of chemical stability over the full (0–14) pH-range and thermal stability up to 120 °C. The membrane consists of polyvinylidene fluoride grafted with polystyrene sulfonic acid. The optimum membrane showed water permeances of 2.4 L h −1 m −2 bar −1 while retaining NaCl, MgSO4 and Rhodamine B (479 Da) for respectively ≈60%, ≈80% and >96%.